Pengaruh suplementasi glisin terhadap kadar serum transferrin receptor (stfr) dan kadar hemoglobin (hb) - Ayu Z, Dian (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2015)
Background: Iron deficiency anemia ( IDA) is still become a health problem in female adolescents. Iron supplementation only as a treatment for IDA still can not reach an optimum results. With that result, there was necessary to developing a strategy for iron supplementation, once treatment with glicyne .Objective: to describe the effect of glycine supplementation on serum transferrin receptor (sTfR) levels and Hemoglobin (Hb) levels in female teenagers with IDA.Methods: This study was quasi experimental, pre post test control group design. The population was female teenagers age 12 – 18 years, Hb < 12 mg/dl, sTfR > 18,4 nmol/L, involving 50 subjects, devided into two groups. The first group was experiment group that given the supplement of 60 mg iron and 1 gr glycine a day for 4 weeks. The second group was control group that given the supplement of only 60 mg iron a day for 4 weeks. The data were analyzed with bivariate test, paired t test, independent t test.Results: There was significantly lower decreased of sTfR levels in treatment group 6,923±10,13 nmol/L than control group 0.809,65±9,076 nmol/L with p=0,008, and significant increased of Hb levels in both treatment group 0,79±1,15 mg/dl and control group 0,22±0,48 mg/dl with p=0,03. Conclusion: Glycine supplementation for 4 weeks decreased sTfR levels in female teenagers with IDA before controlled by vitamin c intake (p=0,04) and after controlled by vitamin c intake variable (p=0,002) and increased Hb levels before controlled by vitamin c intake (p=0,02) and after controlled by vitamin c intake variable (p=0,04).